Juan de Bolonia y Fadrique Furió Ceriol: la ortodoxia doctrinal frenta a la ortodoxia evangélica (Minerva. Revista de Filología Clásica, 2019)
The publication in 1556 of the dispute Bononia siue de libris sacris in uernaculam linguam couertendis libri duo that took place one year before in Louvain, between the native of Valencia F. Furió Ceriol and Johannes of Bologne represents one of the most outstanding landmarks concerning the polemic of the time about the vernacular translation of the Bible. We can assert this because in this book we find the confrontation of the two most outstanding positions of the time regarding the Holy Scriptures and the Faith: the one of Furió, defender of the most extreme spiritualism, that represents the Christianism concerned about the evangelic orthodoxy, and the one of Johannes of Bologna, whose main interest was to preserve the doctrinal unity of the faith by transforming in theology the reading and the explanation of the Bible.